Double appendix with appendicitis: case report - Baimakhanov, Abilay N.; Smagulov, Alibek M.; Otegen, Sungat M.; Kozhakhmetov, Temirkhan K.; Raiymkhanov, Aidar D.; Almatayev, Ulan K.; Otegenova, Aruzhan M. (International Surgery Journal, 2021)
The frequency of doubling of the appendix, according to the literature, is about 0.004% of the number of appendectomies. According to the literature, there were about 100 cases, of which 15 were complicated by the acute form. Doubling can be partial, complete or of several types: a shoot in the form of a double-barreled gun; "avian" in which there are two developed processes located on both sides of the cecum; and one process is located in its usual place, and the other, as a rule, rudimentary, is located along one of the muscle bands. Doubling of the appendix can be in the cecum or in the duplication of the cecum. It was first described and systematized in 1936 by Cave, then in 1962 by Wallbridge, then in 1993 by Biermann.